EVALUASI INSPEKSI UMUM TERENCANA BERDASARKAN INTERNATIONAL SAFETY RATING SYSTEM DALAM PENERAPAN SAFETY PATROL (Studi di PT. Dok dan Perkapalan Surabaya (Persero)) - Zulfia Nita Jamila (JURNAL PENELITIAN KESEHATAN, 2017)
Planned inspection is one of the efforts made to combat workplace accidents and occupational diseases. One type of planned inspection is planned general inspections, a thorough inspection carried out which includes assessment of the safety and health aspects. This inspection is important to identify the physical condition to compliance of companies that have been set. This study aims to determine the level of compliance with the general planned inspection based on the International Safety Rating System (ISRS) in PT. Dok dan Perkapalan Surabaya (Persero).This research is a cross sectional which is descriptive based on the analysis method. This research was conducted in-depth interviews and a review of documents related to the implementation of planned public inspection in PT. Dok dan Perkapalan Surabaya (Persero) based on the sub-element of planned general inspection in third element ISRS.The results showed that the percentage of the level of fulfillment of general planned inspection in PT. Dok dan Perkapalan Surabaya (Persero) amounted to 85.7%. This sub-element can’t be fully achieved due to the absence of identified potential hazard classification and the unavailability of an inspection checklist that is used for each area / structure requiring inspection.Keywords: general planned inspection, international safety rating system